Indoor exposure levels of radon in dwellings, schools, and offices in China from 2000 to 2020: A systematic review. (25th August 2021) - Su, Chunxiao; Pan, Minyi; Zhang, Yinping; Kan, Haidong; Zhao, Zhuohui; Deng, Furong; Zhao, Bin; Qian, Hua; Zeng, Xiangang; Sun, Yuexia; Liu, Wei; Mo, Jinhan; et al.
Abstract: After decades of development, the indoor environment in China has changed. A systematic review was conducted from peer‐reviewed scientific papers with field test data of indoor radon in China from 2000 to 2020 for three types of buildings. The mean concentrations of indoor radon for dwellings, school buildings, and office buildings are 54.6, 56.1, and 54.9 Bq/m 3 . The indoor radon concentration was related to seasons, climate regions, ventilation, decoration, and other factors such as soil and outdoor air. Colder seasons, especially in severe colder areas of China, newer decorated buildings, closed windows, and doors were all associated with higher indoor radon concentrations. Variables like climate region and ventilation showed statistical significance in the correlation analysis. Regarding the increasing trend of indoor radon concentration in China during the last two decades, further study of indoor radon is necessary especially for school buildings and office buildings, and will help access its environmental burden of disease in China more accurately.